Anti Aging Therapy: Various Alignments to Control Premature Aging - SHIVANAND PANDEY; VIRAL DEVMURARI; MANISH GOYANI; RAKHASIYA BHAVIKA (International Journal of Pharma and Bio Sciences, 2010)
Aging changes occur to molecules (DNA, proteins, lipids), to cells and to organs. Diseases of old age (diseases which increase in frequency with age, such as arthritis, osteoporosis, heart disease, cancer, Alzheimer’s Disease, etc.) are often distinguished from aging per se. Some gerontologists prefer to use the word senescence because "aging" implies that the passage of time necessarily results in deterioration (biological entropy) which is certainly not true during the early, developmental, time of life (before the age of 10 or 12 in humans). Human beings reach a peak of growth and development around the time of their mid 20s. Aging is the normal transition time after that flurry of activity. Although there are quite a few age-related changes that tax the body, disability is not necessarily a part of aging. Health and lifestyle factors together with the genetic makeup of the individual, and determines the response to these changes.